2013
DOI: 10.1212/wnl.0b013e31827b1ae0
|View full text |Cite
|
Sign up to set email alerts
|

Depression in epilepsy

Abstract: Objective: To estimate the prevalence of depression in persons with epilepsy (PWE) and the strength of association between these 2 conditions.Methods: The MEDLINE (1948-2012, EMBASE (1980EMBASE ( -2012, and PsycINFO (1806PsycINFO ( -2012 databases, reference lists of retrieved articles, and conference abstracts were searched. Content experts were also consulted. Two independent reviewers screened abstracts and extracted data. For inclusion, studies were population-based, original research, and reported on epil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
216
3
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(254 citation statements)
references
References 49 publications
20
216
3
6
Order By: Relevance
“…A recent systematic review and meta-analysis of depression in 29,891 people with epilepsy showed an overall prevalence of active depression of 23.1%. 15 Cognitive impairment has long been associated with intractable epilepsy. A study in 136 patients with refractory epilepsy found that "cognitive decline was severe and occurred across a wide range of cognitive functions."…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of depression in 29,891 people with epilepsy showed an overall prevalence of active depression of 23.1%. 15 Cognitive impairment has long been associated with intractable epilepsy. A study in 136 patients with refractory epilepsy found that "cognitive decline was severe and occurred across a wide range of cognitive functions."…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, depression represents one of the most common psychiatric disorders in PWE, with a point prevalence ranging from 12-37% in community settings [3]. In clinical studies, depressive symptoms in epilepsy have been associated with several variables such as poor seizure control, duration of epilepsy, having complex partial seizures or temporal lobe epilepsy, unemployment and the use of antiepileptic polytherapy.…”
Section: Editorialmentioning
confidence: 99%
“…December 22, 2014|Volume 4|Issue 4| WJP|www.wjgnet.com has often been reported, and epileptic patients frequently show depressive symptoms, but a recent systematic review and meta-analysis of nine studies including 29891 patients with epilepsy [40] reported a global prevalence of actual/past-year depression of only 23.1%. The high prevalence of depression found in our patients could be due to the fact that depression was diagnosed using a self-report instrument rather than clinical assessment.…”
mentioning
confidence: 99%
“…The high prevalence of depression found in our patients could be due to the fact that depression was diagnosed using a self-report instrument rather than clinical assessment. Significant heterogeneity in the results of ascertaining depression using different methods has been reported [40] . Overall, the current findings were only partially in line with those of Jehi et al [41] , who analyzed data from 1931 subjects affected by drug-resistant and medicallycontrolled epilepsy during one year of follow-up and found that depression, together with seizure severity, was a major predictor of QOL in epileptic patients.…”
mentioning
confidence: 99%